BRAC annual review, 1990 - BRAC (© BRAC, 2016)
This report comments on performance to physical targets and performance to financial budgets during the first nine months of 1990. Inevitably, there are variations, but we did not identify any which we judge need be of major concern to donors. The general record is of greater rather than lesser achievement in relation to what was planned.